Catalyst-free fluorinative alkoxylation of alkenes. Issue 45 (8th November 2018) - Hou, Hong; Li, Hengxue; Xu, Yue; Tang, Daliang; Han, Ying; Yan, Chaoguo; Chen, Xiaoyun; Zhu, Shaoqun
Abstract: The fluorinative alkoxylation of simple alkenes under catalyst-free conditions was achieved. Various substituted olefins, including terminal and internal alkenes, and oxygen-containing nucleophiles were compatible with the standard conditions, and gave a variety of β-fluoroethers in good to excellent yields. Notably, the alkynyl and chloride-containing nucleophiles were well tolerated. In addition, acetic acid and TsNH2 could be also used as nucleophiles and successfully afforded the desired products in good yields. Graphical abstract: